(untitled) (African Journal of Biomedical Research, 2021)
The “One Primary Health Care (PHC) per Ward” policy is an important health care component for achieving health for all. This study assesses the functionality, successes and challenges in the implementation of ‘one PHC per ward’ policy in Ekiti State, Nigeria. In-depth and key informant interview guides serve as qualitative research instruments for data collection. Relevant information was sourced from different stakeholders, including the Executives of the State Primary Health Care Development Agency (SPHCDA), the Local Government Chairmen, the Heads of Departments in PHCs, Staff of PHCs and patients who visited PHC facilities, amounting to twenty-five in-depth and seven key informant interviews. Although all the wards assessed had at least one PHC facility, none of the PHC facilities visited met the minimum standards recommended by the National Primary Health Care Development Agency (NPHCDA). PHC facilities located in the rural areas had fewer infrastructural and human resources than those in the urban area. Routine immunization exercises were improved across the PHC facilities as the Universal Drug Revolving Scheme adopted by the PHCs was successful, largely because of the re-investment of both principal and profit into the purchase of drugs. Results suggest that while routine immunization as an aspect of PHC services had received remarkable successes, the PHC facilities suffered from inadequate equipment and personnel. There is need for a political will and concerted actions that are designed to improve PHC facilities if PHCs are to realize the objectives for setting them up.